COMPUTATION OF OPTIMAL UNSTABLE STRUCTURES FOR A NUMERICAL WEATHER PREDICTION MODEL - Buizza, R; Tribbia, J; Molteni, F; Palmer, T (1993)
Numerical experiments have been performed to compute the fastest growing perturbations in a finite time interval for a complex numerical weather prediction model. The models used are the tangent forward and adjoint versions of the adiabatic primitive-equation model of the Integrated Forecasting System developed at the European Centre for Medium-Range Weather Forecasts and Meteo France. These have been run with a horizontal truncation T21, and 19 vertical levels. The fastest growing perturbations are the singular vectors of the propagator of the forward tangent model with the largest singular values. -from Authors